Pengaruh Pemberian Insentif Dan Upah Terhadap Hasil Kerja Karyawan Pada PT. Rimba Raya Lestari Di Kecamatan Loa Kulu - Eka Norjanah; Achmad Jais; Johansyah Johansyah (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2019)
Abstract :PT. Rimba Raya Lestari is one of the companies engaged in the industry and trade plywood (plywood) is located in the street Yos Sudarso. 18 Village Jembayan District Loa Kulu. The existing system of incentives at PT. Rimba Raya Lestari is to apply the system of achievement of predetermined targets with the amount of wages or salaries that are adjusted to the number of productivity successful employees do in the day. The number of population in this study amounted to 70 permanent employees of the production and the number of samples used amounted to 70 employees. Analyzer tool in this research is multiple regression analysis that is Test of t and Test F with help of Program SPSS For Window version 20.1 The results of F test calculations can be said incentive variables (X1) and wages (X2) simultaneously (simultaneously) able to show the effect on the work of employees. Then the first hypothesis states that